Cerro de la Silla viewed from Monterrey, Mexico - Murrow, Janet Brewster (Tufts Archival Research Center, 2014)
negatives (photographic). From Janet and Edward R. Murrow's honeymoon trip. Photograph appears in photo album, MS225.002.00010, p. 031